Claiming Union Widowhood : Race, Respectability, and Poverty in the Post-Emancipation South - Brimmer, Brandi Clay, 1973- (Book collections on Project MUSE., 2020)
"In Claiming Union Widowhood, Brandi Clay Brimmer analyzes the US pension system from the perspective of poor black women during and after the Civil War. Reconstructing the world of New Bern, North Carolina's grassroots pension network through a broad range of historical sources, she outlines the struggles of mothers, wives, and widows of black Union soldiers to claim pensions in the face of evidentiary obstacles and personal scrutiny. Brimmer exposes and examines the numerous attempts by the federal government to exclude black women from receiving the federal pensions promised to the relatives of dead or maimed Union soldiers. Her analyses illustrate the complexities of social policy, law administration, and the interconnectedness of race, gender, and class formation. Expanding on previous analyses of pension records, Brimmer offers an interpretive framework of emancipation and the freedom narrative that places black women at the forefront of demands for black citizenship"--